2013
DOI: 10.1002/cssc.201300438
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of Nonaqueous Silylamines for Efficient CO2 Capture

Abstract: A series of silylated amines have been synthesized for use as reversible ionic liquids in the application of post‐combustion carbon capture. We describe a molecular design process aimed at influencing industrially relevant carbon capture properties, such as viscosity, temperature of reversal, and enthalpy of regeneration, while maximizing the overall CO2‐capture capacity. A strong structure–property relationship among the silylamines is demonstrated in which minor structural modifications lead to significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 19 publications
1
42
0
Order By: Relevance
“…It is concluded that, in addition to the expected DBU salt of the carbamate (7), an additional species is also present in the reaction mixture. Employing additional NMR experiments, the structure of this species was postulated to be the DBU salt of benzylbicarbamate (8) shown in Figure 8. The experimental details and accompanying interpretation are presented as follows.…”
Section: Reaction Of Benzylamine With 1 Equivalent Of Dbumentioning
confidence: 99%
See 2 more Smart Citations
“…It is concluded that, in addition to the expected DBU salt of the carbamate (7), an additional species is also present in the reaction mixture. Employing additional NMR experiments, the structure of this species was postulated to be the DBU salt of benzylbicarbamate (8) shown in Figure 8. The experimental details and accompanying interpretation are presented as follows.…”
Section: Reaction Of Benzylamine With 1 Equivalent Of Dbumentioning
confidence: 99%
“…In DMSO or DMF the carbamic acid is the primary product. In a solvent such as acetonitrile and an equivalent amount of strong organic base such as DBU, the amidinium benzylcarbamate (7) is the major product along with the amidinium benzylbicarbamate (8). In contrast, if only 0.5 equivalent of DBU is present the major species appears to be the DBU salt of bis-benzylbicarbamate.…”
Section: In Situ Protection Of Amines With Co2mentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 The hypothesis has been that until 60-70% conversion, the ML acts like a solvent to the ionic RevIL species, significantly reducing the ionic and hydrogen bonding between the RevIL. 28,29 The trend with TEtoxySA follows this similar pattern, as shown in Figure 3. However, the conductivity of the system remained relatively constant as a function of conversion, where any change in conductivity is within experimental error.…”
Section: Resultsmentioning
confidence: 99%
“…• C. 28,29,39 The increased CO 2 uptake is due to the formation of carbamic acid. However, literature reports that that the carbamic acid is non-ionic and does not act as a charge carrier.…”
Section: Resultsmentioning
confidence: 99%